Returns to ICT Skills - Simon Wiederhold; Oliver Falck; Alexandra Heimisch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
How important is mastering information and communications technology (ICT) in modern labor markets? Previous research offers no guidance in assessing the labor-market returns to ICT skills, primarily because skill data have been unavailable. We draw on unique data that provide internationally comparable information on ICT skills in 19 countries. Using an instrument that leverages cross-country variation in the technologically determined probability of having Internet access, we find that ICT skills are substantially rewarded in the labor market. Placebo estimations show that exogenous Internet availability cannot explain numeracy or literacy skills, suggesting that our identifying variation is independent of a person s general ability.
Keywords: J31; L96; K23; 330